ANALISIS GAYA BELAJAR SISWA KELAS IV PADA PEMBELAJARAN MATEMATIKA MATERI PENGUKURAN PANJANG DI SDN LEMPONGSARI SEMARANG - Silvi Amalia; Mudzanatun; Aries Tika Damayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research aims to determine the learning styles of class IV students and the factors that influence the learning styles of class IV students in learning mathematics on length measurement material at SDN Lempongsari Semarang. The approach used in this research is a qualitative approach with descriptive research type. The data collection techniques used were observation, interviews and documentation. The research subjects were the class teacher and 10 class IVA students. The results of the analysis showed that of the 10 research subjects, 7 students had a tendency towards a visual learning style, 2 students had a tendency towards an auditory learning style, and 1 student had a tendency towards a kinesthetic learning style. Factors that influence the learning style of class IV students in learning mathematics on length measurement material at SDN Lempongsari Semarang include: internal factors including: physical factors and external factors including: the teacher's learning method in the classroom which uses the lecture method and the location of class IVA which is next to the stairs go up to the top floor and stairs to go down to the bottom floor